2020
DOI: 10.1038/s41598-020-74422-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of REEs with lightweight UAV-based hyperspectral imaging

Abstract: Rare earth elements (REEs) supply is important to ensure the energy transition, e-mobility and ultimately to achieve the sustainable development goals of the United Nations. Conventional exploration techniques usually rely on substantial geological field work including dense in-situ sampling with long delays until provision of analytical results. However, this approach is limited by land accessibility, financial status, climate and public opposition. Efficient and innovative methods are required to mitigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Their results showed with many samples over 50% deviations between airborne and field reflectance values, indicating some issues in the image calibration or the ELM reflectance conversion process. However, the spectral shapes produced using their method were reasonably good (R 2 : 0.85-0.99) and in the related article (Booysen et al, 2020) they showed that the method is good enough for mapping of rare earth elements. Minařík et al (2019) carried out radiometric calibration method based on a laboratory radiometric properties and vicarious correction using an empirical line for a Tetracam μMCA multispectral camera.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed with many samples over 50% deviations between airborne and field reflectance values, indicating some issues in the image calibration or the ELM reflectance conversion process. However, the spectral shapes produced using their method were reasonably good (R 2 : 0.85-0.99) and in the related article (Booysen et al, 2020) they showed that the method is good enough for mapping of rare earth elements. Minařík et al (2019) carried out radiometric calibration method based on a laboratory radiometric properties and vicarious correction using an empirical line for a Tetracam μMCA multispectral camera.…”
Section: Discussionmentioning
confidence: 99%
“…Another development trend of UAV magnetic survey is the use of larger numbers or types of sensors, which means that more information, including gradient tensor, can be obtained [131]. In addition, more information about the research area can be obtained by carrying spectrometers [132,133], electromagnetic sensors [26], [134], cameras [135][136][137], and gamma spectrometers [27,138] with UAVs. Although it is not introduced in this paper, it is important to have a view of these studies.…”
Section: Tendencies Of Uav Magnetic Surveysmentioning
confidence: 99%
“…Tough terrain or outcrops that are difficult to reach on foot or by cars may be quickly surveyed with UAVs from a safe distance with limited manpower on-site, ensuring protection, speed, and quality. The importance of using UAV-based hyperspectral images for geological exploration mapping has been shown by limited studies (Booysen et al, 2020). Hyperspectral sensors have recently begun to be installed on unmanned aerial systems by the Helmholtz Institute Freiberg for Resource Technologies (Jakob et al, 2017).…”
Section: Drone-based Datamentioning
confidence: 99%